The formation and development of OJSC “BSW – Management Company of Holding “BMC”, or 40 years of the Belarusian steel works: a modern view into the past, present and future - S. A. Mozgov; N. I. Anelkin; A. V. Mantsevich; D. G. Voytekhovsky (Литьë и металлургия, 2025)
The year 2024 marks a significant milestone in the history of OJSC “BSW – Management Company of Holding “BMC” as October 15th commemorates the 40th anniversary of the first steel melting and casting on a continuous casting machine in the electric steelmaking shop.The purpose of this article is to provide a comprehensive modern perspective on the technical identity of the enterprise in honor of the 40th anniversary of OJSC “BSW – Management Company of Holding “BMC”. It unites past achievements, the present state, and a vision for mediumand long‑term development. Furthermore, it offers an overview of the establishment and development of Belarusian metallurgy from the 1970s to the 1980s.This review aims to highlight the technical progression, intellectual and technical potential of the enterprise, which were shaped by 40 years of collective effort and international collaboration. The anniversary provides an opportunity to reflect on the origins, analyze achievements to date, and set benchmarks for sustainable mediumand long‑term growth.This article holds unique value and novelty by consolidating diverse theoretical and historical materials on the 40‑year development of the enterprise. It describes the current state, strategic development directions, and includes excerpts from previous publications in scientific and technical journals, offering a theoretical foundation for practical application in engineering, professional, and educational activities.